2022
DOI: 10.5812/modernc-121174
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Coronavirus Anxiety based on Attachment Styles, Resilience, and Life Expectancy in Drug Users

Abstract: Background: The Coronavirus disease 2019 (COVID-19) has had unsolvable psychosocial effects on human beings. The marginalized community, especially drug users, probably suffer from greater psychosocial burden. Objectives: The current study aimed to predict COVID-19-induced anxiety based on attachment styles, resilience, and life expectancy in drug users. Methods: The present study is correlational descriptive-analytical research. The statistical population of this study included all drug users in 2021 who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In previous researches, the relationship between suicidal tendency and maternal bonding had been found to be stronger than this relationship with paternal bonding (65). This finding was consistent with the results of previous studies in terms of the given relationship (21,66,67). This finding may have been explained by the fact that in the first years of a child's life, it's basically the mother who takes care of him and exerts greater influence on his personality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In previous researches, the relationship between suicidal tendency and maternal bonding had been found to be stronger than this relationship with paternal bonding (65). This finding was consistent with the results of previous studies in terms of the given relationship (21,66,67). This finding may have been explained by the fact that in the first years of a child's life, it's basically the mother who takes care of him and exerts greater influence on his personality.…”
Section: Discussionsupporting
confidence: 90%
“…Parental bonding has recently attracted considerable research attention in the field of attachment (20). Studies have shown that parental affectionless control is related to suicidal behavior (21). In addition, studies have shown that parental bonding (22,23) has a direct effect on suicide and is also indirectly associated with a number of factors mediating suicidal ideation, namely shame (24) and guilt (25).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that anxiety can affect cognitive functions and working memory (22,23). Anxiety can be defined as a response to ambiguous and unclear hazards (24). In other words, it is a sense of uneasiness and annoying fear that arises from anticipating a danger with an unclear origin.…”
Section: Introductionmentioning
confidence: 99%